Formation of titanium nitride on γ-TiAl alloys by direct metal-gas reaction - Kittichai Sopunna (2018)
Two alloys, Ti-47Al-2Nb-2Cr (MJ12) and Ti-47Al-2Nb-2Mn + 0.8TiB2(MJ47), were nitrided in purified ammonia for 3.6 × 103-3.6 × 104s (1-10 h) at a temperature range of 800-1,000 °C. The nitridation process can successfully improve alloy hardness which increased with an increase of the nitridation temperature and time. Hardness values of MJ12 and MJ47 with 1,000 °C nitridation for 3.6 × 104s were the highest at 700.5 ± 9.0 and 694.7 ± 21.8 kg mm-2, respectively. The wear rate and friction coefficient were significantly reduced by the nitridation process. Wear resistance of both alloys increased by two orders of magnitude after nitridation compared to the corresponding alloys without nitridation. In addition, the alloys were analyzed using XRD, SEM, EDX and an optical microscope.